2008
DOI: 10.3181/0712-rm-354
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects of Hydrogen Sulfide on IL-6, IL-8 and IL-10 Levels in the Plasma and Pulmonary Tissue of Rats with Acute Lung Injury

Abstract: We examined the possible role of hydrogen sulfide (H2S) in the pathogenesis of oleic acid (OA)-induced acute lung injury (ALI) and its regulatory effects on the inflammatory response. Compared to control rats, the OA-treated rats had decreased partial pressure of oxygen in the arterial blood (PaO2) levels, an increased pulmonary wet/dry weight (W/D) ratio, increased index of quantitative assessment (IQA) score and increased frequency of polymorphonuclear (PMN) cells in the lung 2, 4 or 6 h after OA injection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 49 publications
5
70
0
2
Order By: Relevance
“…IL-6 is closely associated with inflammation, suggesting that SR-A deficiency may negatively affect the expression of IL-6 and TGF-β [38]. H 2 S has been reported to be involved in the negative regulation of inflammatory responses related to a variety of cytokines, thus suggesting that H 2 S has the potential to decrease IL-6 and TGF-β [39]. The findings of Wang et al suggested that SR-A gene knockout protects mice from progressive nephropathy by suppressing the TGF-β pathway [33].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is closely associated with inflammation, suggesting that SR-A deficiency may negatively affect the expression of IL-6 and TGF-β [38]. H 2 S has been reported to be involved in the negative regulation of inflammatory responses related to a variety of cytokines, thus suggesting that H 2 S has the potential to decrease IL-6 and TGF-β [39]. The findings of Wang et al suggested that SR-A gene knockout protects mice from progressive nephropathy by suppressing the TGF-β pathway [33].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma H 2 S is reported to decrease in rats with oelic acidinduced lung injury; exogenous H 2 S increases arterial Pa O 2 , decreases pulmonary edema and infiltration of polymorphonuclear cells, decreases IL-6 and IL-8, but increases IL-10, suggesting that endogenous H 2 S production is decreased in this model of lung injury (93). CSE expression in airway and vascular smooth muscle decreases in ovalbumin-induced lung asthma, whereas exogenous H 2 S alleviates inflammation, restores expiratory flow, and attenuates iNOS activation (22).…”
Section: R301 Therapeutic Potential Of H2smentioning
confidence: 74%
“…Hydrogen sulfide (H 2 S) has also recently been shown to be an important mediator of inflammatory responses and may induce the production or release of substance P [89,90]. Although H 2 S may be proinflammatory, in certain models of ALI, H 2 S production is decreased, and administration of the H 2 S donor sodium hydrosulfide decreased proinflammatory cytokines IL-6 and IL-8, and the resultant ALI [91]. Thus, further studies are needed to better define the interplay of H 2 S and substance P in mediating ALI.…”
Section: Release Of Other Proinflammatory Mediatorsmentioning
confidence: 99%